Legal liability: approaches to understanding - Зелена, Ірина Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article the modern approaches to the understanding of legal liability are systema tized. The features of the methodology of research scientists jurists regarding the nature and essence of legal liability are deter-mined.